First record of the Starry Owlet-Nightjar (Aegotheles tatei) in Indonesian New Guinea (Papua) - Verbelen, Philippe P.J.G. (KUKILA, 2014)
The Starry Owlet-Nightjar Aegotheles tatei, also known as Spangled, Star-spotted or Rand’s Owlet-Nightjar, is one of the least known birds of New Guinea’s lowland rainforests. It was recognized as a distinct species as recently as 2000 and its vocalizations were first documented in 2008. Although hitherto all observations of the species were from Papua New Guinea, its presence in Papua (Irian Jaya) was predictable since the type locality is close to the Indonesian border. A 6-day targeted search for the Starry Owlet-Nightjar was undertaken in lowland forest along the Kali Muyu River. The first Indonesian record for this species was confirmed on 6 October 2012, when a bird was spotlighted and sound recordings of the song and the alarm call were obtained. According to local people, the species may be widespread in the area.